Simple methods for aquaculture pond construction for freshwater fish culture : - Coche, A. G. (Food and Agriculture Organization of the United Nations, 1992)
Main water intake structures, water transport structures, pond inlet structures, pond outlet structures, flood and silt control structures, detailed planning for fish farm construction.